G130 Is inflammatory arthritis of down syndrome (IA-DS) a distinct disease from juvenile idiopathic arthritis (JIA). (May 2019) - Foley, C; Floudas, A; Nair, N; Biniecka, M; Mullan, R; Wilson, G; Killeen, OG; Fearon, U
Abstract : Background: IA-DS prevalence is 18–21-times JIA prevalence. It has an erosive phenotype and frequently presents as polyarticular-RF-negative disease with predominance in the small joints of the hands and wrists. To date little is known about the underlying mechanisms that drive IA-DS pathogenesis; however clinical features suggest that it may be distinct from JIA. We wanted to explore this hypothesis by comparing IA-DS and JIA B-cell subsets and T-cell cytokine profiles; synovial membrane immunohistochemistry; and genetic susceptibility loci i.e. polyarticular-RF-negative JIA susceptibility loci, HLA-DQB1/HLA-DQA2 (rs7775055) and PTPN22 (rs6679677). Methods: Multicolour-flow-cytometry was used to analyse B-cell subsets and T-cell cytokine profiles (IFN-γ, TNF-α) in PBMCs from children with IA-DS (n=10), JIA (n=10) and Down syndrome (n=10), and assessed by Flowjo software analysis. Synovial tissue was obtained through US-guided biopsy and analysed by immunohistochemistry for CD3 (T-cells), CD20 (B-cells), CD68 (macrophages) and FVIII (vascularity) (IA-DS n=3; JIA n=4) using a semi-quantification scoring method. Lining layer hyperplasia was also scored. The team at the Arthritis Research UK Centre for Genetics and Genomics (Manchester) performed genotyping and analysis of HLA-DQB1/HLA-DQA2 and PTPN22 . Results: Flow-cytometry analysis revealed that children with IA-DS had significantly lower numbers of circulating B-cells when compared to children with JIA (p<0.05). However, they had a greater proportion of memory-B-cells when compared to children with Down syndrome and no arthritis (p<0.05). IFN-γ and TNF-α production by CD8+/CD8- T cells was greater in IA-DS compared to JIA (CD8 +IFNγ+p<0.001; CD8 +TNFα+p<0.01; CD8-IFNγ+p<0.05; CD8-TNFα p<0.05). Examination of synovial tissue demonstrated marked increase in synovial lining layer hyperplasia in IA-DS (median 6 (3–9)); JIA (median 3 (2–4)). Higher levels of T-cells, B-cells, macrophages and FVIII (vascularity) in IA-DS were also observed. The MAF (minor allele frequency) for the JIA associated variants rs7775055 ( HLA-DQB1/HLA-DQA2 ) and rs6679677 ( PTPN22 ) were not similar in IA-DS. The minor allele of rs7775055 was absent in IA-DS (p=0.004 when compared to JIA_MAF). The rs6679677 MAFs were significantly different between IA-DS and JIA, p=0.036, OR 2.4. Conclusion: Significant differences were observed in the immune, histological and genetic profiles of IA-DS and JIA suggesting that they may be distinct diseases.